2007
DOI: 10.1002/jclp.20412
|View full text |Cite
|
Sign up to set email alerts
|

Self‐injury: A research review for the practitioner

Abstract: Non-suicidal self-injury is the intentional destruction of body tissue without suicidal intent and for purposes not socially sanctioned. In this practice-friendly review, the authors summarize the empirical research on who self-injures, why people self-injure, and what treatments have demonstrated effectiveness. Self-injury is more common in adolescents and young adults as compared to adults. Common forms include cutting, severe scratching, burning, and banging or hitting; most individuals who self-injure have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

26
460
2
45

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 563 publications
(533 citation statements)
references
References 57 publications
26
460
2
45
Order By: Relevance
“…Self-injurious and suicidal behaviors, however, reported not only strong similarities but also very small differences. Research has indicated that a large number of self-injurers admit that they have also been suicidal (Firestone & Seiden, 1990;Klonsky & Muehlenkamp, 2007;Muehlenkamp & Gutierrez, 2004;Nock et al, 2006). Despite the similarities, research has also revealed obvious differences between the two types of behavior in terms of embodiment, traits, and willingness (Klonsky & Muehlenkamp, 2007;Messer & Fremouw, 2008;Muehlenkamp, 2005).…”
Section: Research-article2015mentioning
confidence: 99%
See 1 more Smart Citation
“…Self-injurious and suicidal behaviors, however, reported not only strong similarities but also very small differences. Research has indicated that a large number of self-injurers admit that they have also been suicidal (Firestone & Seiden, 1990;Klonsky & Muehlenkamp, 2007;Muehlenkamp & Gutierrez, 2004;Nock et al, 2006). Despite the similarities, research has also revealed obvious differences between the two types of behavior in terms of embodiment, traits, and willingness (Klonsky & Muehlenkamp, 2007;Messer & Fremouw, 2008;Muehlenkamp, 2005).…”
Section: Research-article2015mentioning
confidence: 99%
“…Research has indicated that a large number of self-injurers admit that they have also been suicidal (Firestone & Seiden, 1990;Klonsky & Muehlenkamp, 2007;Muehlenkamp & Gutierrez, 2004;Nock et al, 2006). Despite the similarities, research has also revealed obvious differences between the two types of behavior in terms of embodiment, traits, and willingness (Klonsky & Muehlenkamp, 2007;Messer & Fremouw, 2008;Muehlenkamp, 2005). The relationship between gender role conflicts and suicidal behaviors and the relationship between suicidal and self-injurious behaviors signify that the gender patterns in self-injurious behaviors among Chinese adolescents as a boy crisis are probably associated with gender role conflicts.…”
Section: Research-article2015mentioning
confidence: 99%
“…Non-suicidal self-injury (NSSI) is the intentional destruction of body tissue without suicidal intent and for purposes not socially sanctioned (Klonsky & Muehlenkamp, 2007). Examples of NSSI include 'impulsive' acts (preceded by increasing tension, and followed by pleasure, gratification, or relief), such as skin cutting/burning, and 'compulsive' acts (repetitive, seemingly driven, but non-functional motor behaviour acts), such as hair pulling or skin picking (Favazza & Simeon, 1995;Klonsky & Muehlenkamp, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…NSSI is reported to occur in 4-18% of the general population, in 14-68% of individuals with anorexia nervosa (AN), and in 25-55% of individuals with bulimia nervosa (BN), while 54-61% of people with selfinjurious behaviours report current or past ED (Sansone & Levitt, 2002;Jacobson & Gould, 2007;Klonsky & Muehlenkamp, 2007;Kostro et al 2014). The observed link is set against a background of established similarities in epidemiology, underlying mechanisms, and correlates between the two psychopathologies.…”
Section: Introductionmentioning
confidence: 99%
“…In terms of methods, females are more likely to use cutting, whereas males are more likely to use self-hitting or burning (Andover, Primack, Gibb, & Pepper, 2010;Klonsky & Muehlenkamp, 2007).…”
Section: Who Self-injures?mentioning
confidence: 99%